Hong Kong secondary students' perspectives on selecting test difficulty level and learner washback: Effects of a graded approach to assessment. (April 2022) - Tsang, Chi Lai; Isaacs, Talia
This sequential mixed-methods study investigates washback on learning in a high-stakes school exit examination by examining learner perceptions and reported behaviours in relation to learners' beliefs and language learning experience, the role of other stakeholders in the washback mechanism, and socio-educational forces. The focus is the graded approach of the Hong Kong Diploma of Secondary Education English Language Examination (HKDSE-English), incorporated in 2012, that allows test-takers to choose between easier and more difficult sections for reading and listening-integrated skills papers. Inductive coding of focus groups involving 12 secondary students fed into the development of the Washback on Students' Learning questionnaire, which was administered to another 150 learners. Exploratory factor analyses of identified washback effects revealed four major types straddling different settings (classrooms, tutorial schools, learners' personal environment), and seven categories of mediating variables pertaining to learners themselves, other stakeholders, and societal influences. Simultaneous multiple regressions identified influential clusters of mediating variables and showed the strongest predictors for each macro-level washback type varied. At least one intrinsic and one extrinsic factor category significantly contributed to all types, reaffirming learner washback as a socially situated, negotiated construct. Implications related to the consequences, use, and fairness of the graded approach are discussed.